Upgradation of Food Moisture Analyzer using IOT - Mapari, Nafisa; Siddiqui, Salman; Shaikh, Rumi; Srivastav, Rishabh (International Journal of Computer Sciences and Engineering, 2019)
Moisture meters are used to measure the percentage of water in a given substance. This information can be used to determine if the material is ready for use, unexpectedly wet or dry, or in need of further inspection. Food plays a very vital role in our life so it is very important to check the food quality using moisture meter .Moisture plays a very vital role in the daily operations of Food Corporation of India (FCI). With a change in moisture value, computation of storage loss/ gain in food grains gets affected. Hence capturing the moisture value is very essential. Since many food products are bought and sold by weight, moisture content is a key component in ensuring accuracy for purchasing raw materials. Water in food products also affects various characteristics of the product that are important to its taste, texture, color, density, particle size, etc. Generally, moisture is calculated and reading are noted manually and then it is fed in the system then deploy it online. So, the proposed system gives a solution where the readings of the moisture meter are captured and directly fed into Depot Online System (DOS) using wireless transmission. It will reduce the human labor as well reading will be precise as compared traditional system.